Organisational Efficiency or Bureaucratic Quagmire: Do Quality-At-Entry Assessments Improve Project Performance?. Issue 4 (2nd April 2020) - Corral, Leonardo R.; McCarthy, Nancy
Abstract: Do quality-at-entry assessments enhance the delivery of development projects? In this paper we take advantage of approval and execution systems in place at the Inter-American Development Bank (IDB) to examine whether projects that have higher quality-at-entry – captured through grading scores provided by a checklist – perform better in terms of project implementation performance indicators. Implementation indicators include measures based on actual versus planned schedule of activities and cost outlays, as well as per cent of loan disbursed. The analysis suggests higher scores on project logic and economic analyses at entry have had a positive impact on project performance. However, monitoring and impact assessment scores had limited impacts on performance. The evidence supports the hypothesis that the use of a checklist can be an effective framework for assessing quality-at-entry for IDB projects, though there is scope to improve the checklist for certain indicators.